Extra pulmonary COVID-19 manifestations in pediatrics: report of three cases Hospital Edgardo Rebagliati Martins - Peru - Dominguez, Jesus (2020)
Abstract: The objective of this work was to present a series of COVID-19 cases with atypical extra-pulmonary manifestations of the disease. The cases were evaluated by an interdisciplinary team of health personnel from the Pediatric Department of the Edgardo Rebagliati Martins Hospital, of pediatric patients with Covid19, later the data were taken from the clinical history of each patient. Three cases were evaluated, with a satisfactory outcome. The SARS-CoV-2 pandemic is claiming more lives every day, making it necessary to describe cases and their diverse variety of extra-pulmonary presentation, in order to timely identify those infected and take both therapeutic and preventive measures in order to prevent the spread of the disease and achieve its control.